ICAR: endoscopic skull‐base surgery. (22nd July 2019) - Wang, Eric W.; Zanation, Adam M.; Gardner, Paul A.; Schwartz, Theodore H.; Eloy, Jean Anderson; Adappa, Nithin D.; Bettag, Martin; Bleier, Benjamin S.; Cappabianca, Paolo; Carrau, Ricardo L.; Casiano, Roy R.; Cavallo, Luigi M.; et al.
Abstract : Background: Endoscopic skull‐base surgery (ESBS) is employed in the management of diverse skull‐base pathologies. Paralleling the increased utilization of ESBS, the literature in this field has expanded rapidly. However, the rarity of these diseases, the inherent challenges of surgical studies, and the continued learning curve in ESBS have resulted in significant variability in the quality of the literature. To consolidate and critically appraise the available literature, experts in skull‐base surgery have produced the International Consensus Statement on Endoscopic Skull‐Base Surgery (ICAR:ESBS). Methods: Using previously described methodology, topics spanning the breadth of ESBS were identified and assigned a literature review, evidence‐based review or evidence‐based review with recommendations format. Subsequently, each topic was written and then reviewed by skull‐base surgeons in both neurosurgery and otolaryngology. Following this iterative review process, the ICAR:ESBS document was synthesized and reviewed by all authors for consensus. Results: The ICAR:ESBS document addresses the role of ESBS in primary cerebrospinal fluid (CSF) rhinorrhea, intradural tumors, benign skull‐base and orbital pathology, sinonasal malignancies, and clival lesions. Additionally, specific challenges in ESBS including endoscopic reconstruction and complication management were evaluated. Conclusion: A critical review of the literature in ESBS demonstrates at least the equivalency of ESBS with alternative approaches in pathologies such as CSF rhinorrhea and pituitary adenoma as well as improved reconstructive techniques in reducing CSF leaks. Evidence‐based recommendations are limited in other pathologies and these significant knowledge gaps call upon the skull‐base community to embrace these opportunities and collaboratively address these shortcomings.